PEMANFAATAN LIMBAH KAKAO SEBAGAI PAKAN TERNAK KAMBING - Sindu Akhadiarto (Jurnal Rekayasa Lingkungan)
Feed is the main component in livestock industry, and contributes 70% of the total farming cost. Agriculture by-product is one of the alternative feed ingredients for goat feed. The width of cocoa estates in Indonesia in period 2003-2007 shows the highest improvements (43,5 %) than other commodity estates, thus cocoa estates have integrated prospect with livestock industry. Cocoa husk is the most waste of cocoa (73,77 %) and contains raw protein and energy which is not too different with kinggrass, so can substitute green feed more than half. The potential of livestock integrated with the cocoa estates ha a good prospect on the public estate’s development. Cocoa estate has a good prospect to support the integrated with goat farming, however it need s a real concept of the integrated program that work sustainable. The potency of cocoa estate has carrying capacity of 6.05 head goats for 1 hectare area. This is based on the need of the feed from cocoahusk of 1.5 kg/head/day.Keywords : cocoa waste, goat feed